Microtremor HVSR Inversion for Delineating Weathered Granite Layers: A Case Study from Granit Indah, Lampung - Zaenudin, Ahmad; Husni, Yayan M.; Rustadi, Rustadi; Wibowo, Rahmat C; Farduwin, Alhada (ICSIGER- International Conference on Science and Emerging Technology, 2025)
The Horizontal-to-Vertical Spectral Ratio (HVSR) method is an efficient and non-invasive approach for estimating subsurface layer thickness and delineating near-surface geological structures. This study employs HVSRPy, an open-source Python-based tool, to characterize the subsurface stratigraphy of the Granit Indah area in Lampung. Microtremor data were collected at 24 stations using three-component sensors with 30-minute acquisition durations. Processing involved window selection, Fourier transformation, and HVSR curve computation. Dominant frequencies ranging from 0.2 to 5.3 Hz indicate the presence of thick near-surface deposits. Inversion using Dinver resolves three principal layers—topsoil, weathered saprolite, and unweathered granite—with shear-wave velocities of 200–600 m/s. The subsurface model shows strong agreement with Wenner–Alpha resistivity measurements, supporting its reliability. The results demonstrate that HVSRPy provides a robust, time-efficient, and cost-effective workflow for subsurface characterization in regions with limited geophysical data.